Cell of origin in radiation‐induced premalignant thymocytes with differentiation capability in mice conditionally losing one Bcl11b allele. Issue 8 (17th June 2013) - Go, Rieka; Hirose, Satoshi; Katsuragi, Yoshinori; Obata, Miki; Abe, Manabu; Mishima, Yukio; Sakimura, Kenji; Kominami, Ryo
Abstract : Bcl11b is a haploinsufficient tumor suppressor, mutations or deletion of which has been found in 10–16% of T‐cell acute lymphoblastic leukemias. Bcl11b KO /+ heterozygous mice are susceptible to thymic lymphomas, a model of T‐cell acute lymphoblastic leukemia, when γ‐irradiated, and irradiated Bcl11b KO /+ mice generate clonally expanding or premalignant thymocytes before thymic lymphoma development. Cells with radiation‐induced DNA damages are assumed to be the cells of origin in tumors; however, which thymocyte is the tumor cell origin remains obscure. In this study we generated Bcl11b flox/+ ; Lck‐Cre and Bcl11b flox/+ ; CD4‐Cre mice; in the former, loss of one Bcl11b allele occurs in thymocytes at the immature CD4 − CD8 − stage, whereas in the latter the loss occurs in the more differentiated CD4 + CD8 + double‐positive stage. We examined clonal expansion and differentiation of thymocytes in mice 60 days after 3 Gy γ‐irradiation. Half (9/18) of the thymuses in the Bcl11b flox/+ ; Lck‐Cre group showed limited rearrangement sites at the T‐cell receptor‐β ( TCRβ ) locus, indicating clonal cell expansion, but none in the Bcl11b flox/+ ; CD4‐Cre group did. This indicates that the origin of the premalignant thymocytes is not in double‐positive cells but immature thymocytes. Interestingly, those premalignant thymocytes underwent rearrangement at various different sites of the TCRα locus and the majority showed a higher expression of TCRβ and CD8, and more differentiated phenotypes. This suggests the existence of a subpopulation of immature cells within the premalignant cells that is capable of proliferating and continuously producing differentiated thymocytes.